Knowledge First? - McGlynn, Aidan. author. aut Link
XIII, 227 p.
Keywords: According to a long tradition, questions about the nature of knowledge are to be answered by analyzing it as a species of true belief. In light of the apparent failure of this approach, knowledge first philosophy takes knowledge as the starting point in epistemology. Knowledge First? offers the first overview of this approach.